Advanced vibration diagnostic system as the part of helicopter technical maintenance - Mironov, A.; Doronkin, P.; Priklonsky, A.; Podoryashy, D.; Garipov, A. (My University, 2017)
This paper considers different aspects of advanced vibration diagnostic system development, validation, promotion and application. Authors discuss the list of tasks for such system from the helicopter technical maintenance and repair point of interest. Main problems and possible solutions are considered, including uniform diagnostic platform for board and ground systems, life cycle traceability for helicopter aggregates, single survey diagnostics etc. The general view on advanced system is presented, based on the state-of-the-art and advanced techniques of vibration diagnostics and SHM. Resolution levels for helicopter power unit aggregates are considered based on solutions of the high-resolution diagnostics collected under VibropassportTM brand. Authors discuss operating demonstrators of diagnostic techniques as well as application cases as the main tools for advanced system promotion and market entering.